Fatigue Level Of Chronic Kidney Failure Patients After Undergoing Hemodialysis Therapy - Affin Ari Laksmana; Nina Indriyawati (Poltekkes Kemenkes Surakarta, 2022)
Background: Chronic kidney failure is a terminal illness where the disease cannot be cured, so it requires hemodialysis therapy. Life changes in post-HD patients cause various complications that make patients feel uncomfortable, have insomnia, and feel dizzy and tired. Therefore, it is necessary to measure the level of fatigue using a post-dialysis fatigue scale to anticipate the exhaustion felt by the patient on the subsequent dialysis. Methods: Quantitative research using PLS statistics, the population in this study consisted of 69 residents who had post HD and conducted on 59 samples with purposive sampling. Obtained the results of validity and reliability in the study, composite realiability= 0.902; rho_A= 0.895; discriminant validity=0.650. Collecting data using a questionnaire Post Dialysis Fatigue Scale (PDFS). The study was conducted in February 2022. Results: The results showed that most respondents felt severe fatigue, as many as 44 people (74.6%) after undergoing hemodialysis therapy. The items that respondents felt most about fatigue levels included feeling dizzy, headache, no appetite, chest aches, and pains. In addition, the majority of respondents aged ≥50 years, 26 respondents (70.3%) felt severe fatigue. While the majority of respondents who underwent hemodialysis for ≥12 months, namely as many as 35 respondents (76.1%), felt extreme fatigue. Conclusion: Most respondents were dominated by men with an average blood pressure of 140/88 mmHg and were in the category of severe fatigue.